The Relationship between Subjective Well-being and Social Support among Jordanian University Students - Ahmad M. Mahasneh (Psychology in Russia: State of Art, 2022)
Background. Although the interest in subjective well-being has flourished during recent decades, there is a general lack of research into this subject throughout the Arab world, and in the Jordanian academic environment in particular. Objective. The present study aimed to identify any significant gender differences in the level of subjective well-being, and to examine the relationship between subjective well-being and social support among a sample of Hashemite University students. Design. The study sample comprised 679 male and female undergraduate students from the Hashemite University chosen by purposive method. The College Student Subjective Well-being Questionnaire and Multidimensional Scale of Perceived Social Support were used to collect the data. Results. The results showed no significant differences in the level of subjective wellbeing due to the gender variable, but indicated significant differences between genders in satisfaction with academics and school connectedness. The results also showed a positive relationship between subjective well-being and social support. Conclusion. The current study contributes to enriching the theoretical literature related to gender differences in the level of subjective well-being of Jordanian university students and to examining the relationship between subjective well-being and social support.